2019
DOI: 10.1177/1120672119896419
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial etiology and antimicrobial resistance trends in ocular infections: A 30-year study, Turin area, Italy

Abstract: Purpose: Bacterial ocular infections can result in loss of all or part of the ocular structures, contributing to a high disability charge. Local surveillance of etiology and susceptibility patterns is crucial for an appropriate empiric management of ocular infections. The aim of this study was to analyze of bacterial spectrum in culture-proven ocular infections and trends of antimicrobial susceptibility patterns. Methods: A monocentric retrospective study was performed including ocular infection cases diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
(67 reference statements)
3
23
2
Order By: Relevance
“…For example, among the various ocular microbiology investigations conducted across Ethiopia, by Ayebubizu et al 5 , Belyhun et al 2 , Assefa et al 10 as well as Getahun and colleagues 8 the proportionate distribution of Gram-negatives were similar to Gram positives. Of note, whereas the magnitude of Gram-negative bacteria etiology found in Australia 21 , Iran 20 and Italy 24 were not equivalent to our ndings as well as studies in parts of Ethiopia, the proportion estimates reported were relatively higher. There exist regional variations in the patterns of distribution of Gram-negative bacteria, however, the higher prevalence in our study are ascribed to hygiene as the primary mode of transmission of these enteric bacteria are through oral-fecal contamination.…”
Section: Bacteria Etiology Of External Ocular and Periocular Infections Among Study Participantscontrasting
confidence: 99%
See 1 more Smart Citation
“…For example, among the various ocular microbiology investigations conducted across Ethiopia, by Ayebubizu et al 5 , Belyhun et al 2 , Assefa et al 10 as well as Getahun and colleagues 8 the proportionate distribution of Gram-negatives were similar to Gram positives. Of note, whereas the magnitude of Gram-negative bacteria etiology found in Australia 21 , Iran 20 and Italy 24 were not equivalent to our ndings as well as studies in parts of Ethiopia, the proportion estimates reported were relatively higher. There exist regional variations in the patterns of distribution of Gram-negative bacteria, however, the higher prevalence in our study are ascribed to hygiene as the primary mode of transmission of these enteric bacteria are through oral-fecal contamination.…”
Section: Bacteria Etiology Of External Ocular and Periocular Infections Among Study Participantscontrasting
confidence: 99%
“…Globally, eye infections of bacteria origin remain a signi cant contributor to ocular morbidity and blindness, and the burden is increasing 1,2 . Further, results from ocular microbial studies across different populations show no obvious pattern in prevalence estimates (ranging from 21.8-82.5%) across Africa [2][3][4][5][6][7][8][9][10][11][12] , Asia [13][14][15][16][17][18][19][20] , Australia 21,22 , Europe [23][24][25] and North America 26 . Similarly, the bacterial etiology speci cally proportion and nature of Gram bacteria as well as the species of bacteria commonly implicated in ocular and periocular infections vary across geographical regions and settings 2-13,15−20,22,24−26 .…”
Section: Introductionmentioning
confidence: 99%
“…e most common bacterial pathogens, involved in pediatric ocular infection are coagulase-negative Staphylococci (CoNS), Staphylococcus aureus (S. aureus), Streptococcus pneumoniae, Pseudomonas aeruginosa (P. aeruginosa), and Haemophilus influenzae [11]. Gram-positive bacteria are primarily responsible for pediatric ocular infection [12]. A prospective study conducted in the United States has revealed that 65% of children have ocular infections caused by Gram-positive bacteria [13].…”
Section: Introductionmentioning
confidence: 99%
“…124 A similar study from Italy, with a 30-year follow up , reported an increasing rate of resistance of S. aureus to antibiotics, from 21 per cent in 2003 to 38 per cent in 2015, as well as for S. pneumoniae (7.4 per cent to 23.3 per cent). 125 In the same study, multidrug (resistant to at least one aminoglycoside and one fluoroquinolone) resistance rates of S. aureus were significantly increased from 8.7 per cent to 12 per cent, as was resistance in isolates of Enterobacteriaceae (24.5 per cent to 34.6 per cent). 125 Retrospective studies have reported increasing rates of MRSA.…”
Section: Ocular Microbial Resistancementioning
confidence: 87%
“…125 In the same study, multidrug (resistant to at least one aminoglycoside and one fluoroquinolone) resistance rates of S. aureus were significantly increased from 8.7 per cent to 12 per cent, as was resistance in isolates of Enterobacteriaceae (24.5 per cent to 34.6 per cent). 125 Retrospective studies have reported increasing rates of MRSA. 69,126 An increasing prevalence of ocular MRSA infections from nine per cent to 38 per cent over a 10-year period (2007-2017) of study duration has been reported.…”
Section: Ocular Microbial Resistancementioning
confidence: 87%